Le tribunal pénal international pour le Rwanda - La justice trahie (Note) - Philpot, John (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1996)
On November 8,1994, the Security Council of the United Nations adopted Resolution 955 creating an ad hoc international criminal tribunal to judge individuals responsible for violations of international humanitarian law committed in Rwanda between January 1, 1994 and December 31, 1994. In its form and structure, the Tribunal does not respect basic legal requirements required of a tribunal set up in international law. Us mandate - limited in time, in scope of potential indictment, and in jurisdiction to violations of international humanitarian law - mil prevent any light from being shed on the real issue raised by the Rwandan conflict, namely that of armed military intervention in Rwanda from Uganda. It will likely lead to the reinforcement of a one-sided view of the crisis in Rwanda and legitimate further unilateral interventionist policies in Africa and elsewhere. The Tribunal will institutionalize the de facto impunity for the members and supporters of the present government of Rwanda who undoubtedly committed many serious crimes between October 1, 1990 and the present.